Turtles, Tablets, and Boxes: Computer Technology and Education in the 1970s. - Petrick, Elizabeth (Information & Culture, 2023)
One of the most powerful ideas behind the potential of computer technology is that it could revolutionize education. To understand this idea historically, this article brings together computer science researchers with theories of education and childhood development. These researchers—Seymour Papert at MIT and Alan Kay and Adele Goldberg at Xerox's Palo Alto Research Center—drew on a group of mid-twentieth-century education theorists. These cases offer a window into how computer researchers have read and interpreted scientific theories about education and childhood development that then make their way into computer technology or fail to do so entirely.